2013
DOI: 10.3163/1536-5050.101.3.010
|View full text |Cite
|
Sign up to set email alerts
|

Access of primary and secondary literature by health personnel in an academic health center: implications for open access

Abstract: When it is available, health personnel in a clinical care setting frequently access the primary literature. While further studies are needed, this preliminary finding speaks to the value of the National Institutes of Health public access policy and the need for medical librarians and educators to prepare health personnel for increasing public access to medical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
(38 reference statements)
3
6
0
1
Order By: Relevance
“…The prevalence of PubMed as the most commonly used database in information retrieval training aligns with Just's and Brettle's earlier findings [4,9] and with practices observed in clinical settings [44]. Also in agreement with previous research on the varied use of information resources in practice, we noted the inclusion of additional information resources beyond PubMed [45], such as DynaMed, ACP Journal Club, and UpToDate.…”
Section: Resources and Skills Trainedsupporting
confidence: 87%
“…The prevalence of PubMed as the most commonly used database in information retrieval training aligns with Just's and Brettle's earlier findings [4,9] and with practices observed in clinical settings [44]. Also in agreement with previous research on the varied use of information resources in practice, we noted the inclusion of additional information resources beyond PubMed [45], such as DynaMed, ACP Journal Club, and UpToDate.…”
Section: Resources and Skills Trainedsupporting
confidence: 87%
“…Proliferation of medical research—in concert with expanding access to the Internet—has dramatically magnified the amount and availability of medical information . Our results support prior research indicating that medical information may be increasingly accessed by providers via interaction with online summary databases, rather than through electronic sources of primary medical literature or digital textbooks …”
Section: Discussionsupporting
confidence: 88%
“…1 Our results support prior research indicating that medical information may be increasingly accessed by providers via interaction with online summary databases, rather than through electronic sources of primary medical literature or digital textbooks. 3,6,7 Our study has implications for the practice of hospital-based medicine. Our findings may reflect evolving provider preferences for synthesized medical information that can be translated efficiently to clinical practice.…”
Section: Discussionmentioning
confidence: 94%
“…Although an earlier study found that nurses have limited skills and encounter difficulties when searching for relevant virtual information (Verhoeven et al, 2010), the current study suggests, instead, that nurses employ unique patterns of e-health usage to retrieve information. These patterns are based on personal experience, confidence, and preferences for certain electronic resources or formats, a trend that is supported by more recent studies (Chiu & Tsai, 2014;Hains et al, 2012;Jones et al, 2011;Maggio, Steinberg, Moorhead, O'Brien, & Willinsky, 2013). The current study results emphasize that e-health cannot entirely replace traditional methods of professional learning and information exchange but, instead, are most beneficial when used as a complement to existing resources.…”
Section: Discussionsupporting
confidence: 75%